The safety and efficacy of N-acetylcysteine as an augmentation in the treatment of obsessive-compulsive disorder in adults: a systematic review and meta-analysis of randomized clinical trials - Eghdami, Shayan; Eissazade, Negin; Heidari Mokarar, Mohsen; Boroon, Mahsa; Orsolini, Laura; Shalbafan, Mohammadreza (Frontiers in Psychiatry, 2024)
Background: Obsessive-compulsive disorder (OCD) ranks as the fourth most prevalent psychiatric disorder, with selective serotonin reuptake inhibitors (SSRIs) as its mainstay pharmacological treatment. However, approximately 40 to 60% of patients do not adequately respond to initial treatment, highlighting the need for alternative options. N-acetylcysteine (NAC) is one of the several medications that have been used in augmentation with SSRIs to enhance their efficacy. Objectives: We aimed to investigate the safety and efficacy of NAC, a glutamate-modulating agent, as an augmentation in the treatment of moderate to severe OCD.We conducted a thorough search across PubMed, Scopus, Web of science, and ProQuest to identify relevant trials published until December 2023. The primary outcome of interest was the mean difference between the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) scores before and after administrating augmented NAC among patients with moderate to severe OCD. Furthermore, we compared the occurrence of adverse drug events between the experimental and control groups. Results: We included six randomized controlled trials with 195 patients. The results of our study indicated a positive outcome for the experimental group in terms of the total Y-BOCS score when using the medication for a period of five to eight weeks (p-Value = 0.05). However, no significant difference was observed for durations shorter than five weeks or longer than 12 weeks. Additionally, no significant difference was found between the two groups in terms of the obsession and compulsion Y-BOCS scores. Furthermore, no significant differences were observed in terms of adverse events. Conclusion: Augmentation of NAC with SSRIs may benefit patients with moderate to severe OCD. However, it is necessary to conduct additional multi-center trials over extended periods to develop a comprehensive strategy for action.